Deleterious and protective effects of epothilone-D alone and in the context of amyloid β- and tau-induced alterations - Ángel Abdiel Robles-Gómez; Ángel Abdiel Robles-Gómez; Benito Ordaz; Jonathan-Julio Lorea-Hernández; Fernando Peña-Ortega (Frontiers in Molecular Neuroscience, 2023)
Amyloid-β (Aβ) and hyperphosphorylated tau (P-tau) are Alzheimer’s disease (AD) biomarkers that interact in a complex manner to induce most of the cognitive and brain alterations observed in this disease. Since the neuronal cytoskeleton is a common downstream pathological target of tau and Aβ, which mostly lead to augmented microtubule instability, the administration of microtubule stabilizing agents (MSAs) can protect against their pathological actions. However, the effectiveness of MSAs is still uncertain due to their state-dependent negative effects; thus, evaluating their specific actions in different pathological or physiological conditions is required. We evaluated whether epothilone-D (Epo-D), a clinically used MSA, rescues from the functional and behavioral alterations produced by intracerebroventricular injection of Aβ, the presence of P-tau, or their combination in rTg4510 mice. We also explored the side effects of Epo-D. To do so, we evaluated hippocampal-dependent spatial memory with the Hebb–Williams maze, hippocampal CA1 integrity and the intrinsic and synaptic properties of CA1 pyramidal neurons with the patch-clamp technique. Aβ and P-tau mildly impaired memory retrieval, but produced contrasting effects on intrinsic excitability. When Aβ and P-tau were combined, the alterations in excitability and spatial reversal learning (i.e., cognitive flexibility) were exacerbated. Interestingly, Epo-D prevented most of the impairments induced Aβ and P-tau alone and combined. However, Epo-D also exhibited some side effects depending on the prevailing pathological or physiological condition, which should be considered in future preclinical and translational studies. Although we did not perform extensive histopathological evaluations or measured microtubule stability, our findings show that MSAs can rescue the consequences of AD-like conditions but otherwise be harmful if administered at a prodromal stage of the disease.